2020
DOI: 10.1017/s1041610219001881
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing ‘meaningfulness’ of functional assessments: UK adaptation of the Amsterdam IADL questionnaire

Abstract: Objective: Commonly used measures of instrumental activities of daily living (IADL) do not capture activities for a technologically advancing society. This study aimed to adapt the proxy/informant-based Amsterdam IADL Questionnaire (A-IADL-Q) for use in the UK and develop a self-report version.Design: An iterative mixed method cross-cultural adaptation of the A-IADL-Q and the development of a self-report version involving a three-step design: (1) interviews and focus groups with lay and professional stakeholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…However, WA scoring is much simpler, and this score is already available in the online platform used for IADL assessments. The authors of the validation study of the UK version of A-IADL-Q also used the WA scoring method in part of their study, which was in high concordance with the IRT scoring [23]. Our study showed that both scoring methods could be used in clinical practice and research with similar sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 63%
“…However, WA scoring is much simpler, and this score is already available in the online platform used for IADL assessments. The authors of the validation study of the UK version of A-IADL-Q also used the WA scoring method in part of their study, which was in high concordance with the IRT scoring [23]. Our study showed that both scoring methods could be used in clinical practice and research with similar sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 63%
“…personal finances and using new personal technology) which may be indicators of impending dementia [33]. The Amsterdam IADL scale has undergone international validation studies [34,35].…”
Section: Neurodegeneration (N)mentioning
confidence: 99%